2017
DOI: 10.1111/ffe.12660
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the effect of pre‐bond contamination with de‐icing fluid and ageing on the fracture toughness of composite bonded joints

Abstract: The scope of the present work is to experimentally investigate the effect of pre‐bond contamination with de‐icing (DI) fluid and the combined effect of DI fluid and hygrothermal ageing on the fracture toughness of carbon fibre reinforced plastic bonded joints. These scenarios could occur in the implementation of an adhesively bonded patch repair in a composite aircraft structural part. To this end, mode I and mode II fracture toughness tests were conducted on contaminated specimens and mode II fracture toughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(57 reference statements)
2
20
0
2
Order By: Relevance
“…Runway de-icing fluid is one of the most commonly encountered fluids that aircraft structures may be exposed to, as it can be swirled from the runway to outer parts of the aircraft [2]. During patch-repairing of composite parts, inadequate cleaning can result to de-icing fluid remains.…”
Section: Pre-bond Contamination Of Cfrpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Runway de-icing fluid is one of the most commonly encountered fluids that aircraft structures may be exposed to, as it can be swirled from the runway to outer parts of the aircraft [2]. During patch-repairing of composite parts, inadequate cleaning can result to de-icing fluid remains.…”
Section: Pre-bond Contamination Of Cfrpsmentioning
confidence: 99%
“…In aerostructures, adhesive bonding is applied in metal-to-metal joints, composite-to-composite joints and composite-to-metal joints both for assembling parts and for patch-repairing. However, application of adhesive bonding in aerostructures is limited for the moment to secondary structural parts that are not load-critical [1,2] due to certification reasons. In the certification requirements for primary composite aircraft structures, it is stated that for bonded joints repeatable and reliable non-destructive inspection techniques (NDI) must be established that ensure the strength of each joint [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, release agent specimens were created by deep-coating of one of the composite plate. In addition, GIC and GIIC tests have been performed by University of Patras, and show that various bonding strength have been obtained [9]- [11].…”
Section: The Experimentsmentioning
confidence: 99%
“…As far as the de-icing fluid is considered it was shown that it has a negative effect on both mode I and mode II fracture toughness of the bonded joints. The increasing level of contamination results in decrease of the mode I and mode II critical energy release rates [3]. In this paper we report results of five techniques employed for assessment of the bonds.…”
Section: Introductionmentioning
confidence: 99%